The future of synodality: how we move forward from here - Colberg, Kristin (Liturgical Press, 2025)
"In The Future of Synodality, readers are introduced to key aspects of the origins of synodality, its theological foundations, and recent expressions. In the second part, readers are encouraged to look towards the future and explore concrete transformations that can catalyze the on-going synodalization of the church-helping those engaged in the synodal process to better understand this historic moment in the church's life and learn how to walk together on the synodal path"--